The first report of two new janiroid isopod species (Asellota, Janiroidea) from the western Indian Ocean - Valiallah Khalaji-Pirbalouty; Manal Abdulrahman Al-Kandari (ZooKeys)
Two new janiroid isopod species, Heterosignum behbehanii sp. nov. and Uromunna alyamanii sp. nov., are described from the Kuwaiti waters, representing the first record of the genera in the western Indian Ocean. Heterosignum behbehanii sp. nov. is distinguished from its congeners by pereonites 2–7 with a pair of short single lateral spine-like processes; the relatively short length of the anterior part of its pleotelson, which accounts for about 0.1 of the total length of the pleotelson; and the stylet with an elongate, downwardly curved, and distally pointed apex. Uromunna alyamanii sp. nov. is equally unique, with the pleotelson bearing two denticles on each lateral margin, pleopod 2 endopod stylet extending beyond the apex of the protopod, and pleopod 4 exopod distal tip with a long plumose seta. This discovery of unique characteristics of the new species significantly enhances our understanding of marine biodiversity in the western Indian Ocean and underscores the importance of further research in this area. The identification keys are provided to all known species of Heterosignum and Indian Ocean Uromunna species.